Sufism in Latin Europe (France, Spain, Italy). - Piraino, Francesco; De-Diego-González, Antonio (Brill, 2023)
The current chapter describes global trends that affect Sufism prior to framing them in local contexts. Although the abovementioned sources of Latin European Sufism are similar across all Western countries, their outcomes often differ in diverse local settings. In order to comprehend both the complexity and common trends among different countries, we discuss Sufism in Latin Europe using eight categories: 1) De-Islamised Sufism; 2) Western esoteric Sufism; 3) Erudite Sufism; 4) Transplanted Sufism; 5) Anti-modern Sufism; 6) Fragmented Sufism; 7) Engaged Sufism; and 8) Public Sufism. These categories are ideal-types (Weber 1968) that could serve as useful instruments in comprehending multifaceted phenomena. The order in which these categories will be presented is both chronological and thematic. All of these categories are intertwined: individual Sufis and Sufi orders could shift from category to category according to the historical and geographical context, hence these categories are not fixed or exclusive. For example, the ʿAlāwiyya, founded at the beginning of the 20 th century in Algeria, developed branches in France composed of Algerian migrants—hence a transplanted Sufism, but at the same time it developed independent branches formed only by European converts that could be described as “Western esoteric Sufism”; furthermore, this Sufi order hosted and hosts several intellectuals who compose “erudite Sufism”; and finally, with the present Shaykh Bentounes it is now transnational, engaged in social and cultural activities connected to interfaith dialogue as forms of “public” Sufism.
Keywords: Misticismo - Islam; Filosofía islámica; Sufismo; Islam; Sufismo en Europa; Pensamiento islámico